Imprisonment of the Debtor in the Jordanian Implementation Law in Comparison to Islamic Jurisprudence and International Covenants - Al- Amayrah, Mohamed Hamed Mohamed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study deals with the provisions of the debtor's imprisonment in the Jordanian This study deals with the provisions of imprisonment of the debtor in the Jordanian Execution Law No. 25 of 2017 and its amendments, in comparison to the Islamic jurisprudence and international covenants. The main problem is the extent to which the debtor may be imprisoned in the Jordanian Execution Law compared to Islamic jurisprudence and international covenants. Analytical approach as it fits in with this study and its nature by interpreting the texts and legal articles in the Jordanian implementation law, Islamic jurisprudence and international conventions and analyzing them in order to deduce the legal and jurisprudential purpose. Hence, the researcher took the approach of comparing the texts R and theories between the Jordanian law and Islamic jurisprudence with international covenants'. At the end of the study, the researcher found that imprisonment has been used in modern terms since it was analyzed by the scholars of Islamic law until it reached the legislative texts in the jurisprudential magazine, which is based on the Jordanian law, as a result of the positive achievements that contributed to the preservation of the rights of individuals (creditors). And that the International Covenant on Civil and Political Rights only provided for debts arising from contractual relations only, without the other sources of obligation addressed by domestic laws and Islamic jurisprudence.The researcher reached a number of conclusions and recommendations. The most important of these results was that the imprisonment of the debtor is an act of compulsion and pressure rather than an end to imprisonment as a punishment, aimed at restricting the debtor to fulfill his obligations to the creditor. Freedoms The legislator has put in place a legal regulation concerning the imprisonment of the debtor surrounded by a number of provisions to prevent abuse by the creditor in order to collect the creditor's money from the debtor. One of the most important recommendations reached by the researcher,The researcher hopes relevant international organizations and organizations to better understand the subject of the debtor's imprisonment, understanding the purpose, objectives and manner of the debtor, and understanding the principle that this detention was initiated after balancing the rights of the financial creditor and the rights of the debtor.
Keywords: imprisonment of debtor; international covenants; law of implementation